Electrodeposition coating material composition comprising composite particles comprising metal-containing catalyst
By using an electrodeposition coating material composition containing cathode-deposited aqueous binder dispersion, pigment paste and composite particles, the resistance of the electrodeposition coating material under phosphate contamination is solved, efficient curing and crosslinking of the coating film is achieved, and good corrosion protection effect is ensured.
Patent Information
- Application Number
- CN202380066195.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-15
- Filing Date
- 2023-08-17
- Publication Date
- 2025-04-29
AI Technical Summary
The existing electrodeposition coating materials are susceptible to phosphate contamination during conventional use, resulting in catalyst degradation, affecting the curing and crosslinking of the coating film, thereby reducing the corrosion protection effect.
An electrodeposition coating material composition comprising a cathode-depositable aqueous binder dispersion, pigment paste and composite particles containing (meth)acrylate-based composite particles capable of maintaining excellent characteristics of the coating film in the presence of a large amount of phosphate.
The resistance of electrodeposited coating materials to phosphate pollution is significantly improved, ensuring that the coating film can be effectively cured and cross-linked during the production process, and maintaining good corrosion protection performance.
Smart Images

Figure BDA0005311754970000151 
Figure BDA0005311754970000171 
Figure BDA0005311754970000181
Abstract
Description
[0001] The present invention relates to a cathodically depositable aqueous electrodeposition coating material composition, the composition comprising at least one binder dispersion (I), the at least one binder dispersion comprising at least one cathodically depositable polymer (a) and at least one crosslinking agent (b); and at least one pigment paste (II), the at least one pigment paste comprising at least one pigment and / or filler (c), wherein the composition further comprises at least one type of composite particles (p), the composite particles comprising at least one metal-containing catalyst (pc) and at least one (meth)acrylate-based polymer (mp), wherein the polymer (mp) is preferably prepared in the presence of the metal-containing catalyst (pc). The present invention also relates to a method for at least partially coating a conductive substrate by cathodic electrodeposition coating, the method comprising at least steps (1) to (5), comprising the step (1) of at least partially immersing the substrate in an electrodeposition coating bath, the electrodeposition coating bath comprising the electrodeposition coating material composition of the present invention. In addition, the present invention relates to a conductive substrate, which is at least partially coated with a baked electrodeposition coating material composition of the present invention and / or is obtainable by the method of the present invention. Finally, the present invention relates to the use of the composite particles (p) for improving the robustness of the electrodeposition coating bath against phosphate contamination. Background Art
[0002] In the automotive industry, metal parts used for manufacturing often have to be protected from corrosion. The requirements to be achieved in terms of corrosion control are very stringent, not least because manufacturers often offer a multi-year guarantee against rust perforation. This corrosion control is usually achieved by coating the parts or the substrates used to manufacture them with at least one coating suitable for this purpose.
[0003] In order to ensure the necessary corrosion control, it is common practice to apply a phosphate pretreatment composition (e.g. a zinc phosphate-based composition) to the metal substrate before applying the electrodeposition coating film. Electrodeposition coating (electrocoating) materials are coating materials comprising a polymer as a binder, a crosslinking agent, a pigment and / or a filler, and often additives. Generally, there are electrocoating materials that can be deposited anodically and can be deposited cathodically. Anodic electrodeposition coating compositions, in particular, comprising metal effect pigments are disclosed, for example, in WO 2006 / 117189 A1. However, cathodically depositable materials are of the greatest importance in industrial coating and in particular in automotive finishing. In cathodic electrodeposition coating, the substrate to be coated is immersed in an electrocoating bath and connected as a cathode. The bath has an anode as a counter electrode. The particles of the electrocoating material are stabilized with a positive charge and deposited on the cathode to form a coating film. After deposition, the coated substrate is removed from the electrocoating bath, rinsed with water and the coating film is baked, i.e. thermally cured. During curing, a chemical reaction occurs and thus a crosslinking of the binder polymer and the crosslinking agent occurs, such as, for example, a crosslinking of hydroxyl and / or amino groups with isocyanates. In order to promote efficient curing and crosslinking reactions, the electrodeposition coating composition usually contains a corresponding catalyst, especially a metal-containing catalyst, like a tin- or bismuth-containing catalyst.
[0004] Cathodically depositable electrocoating materials are known in the prior art, for example from EP 1 041 125 A1, DE 197 03 869 A1 and WO 91 / 09917 A2.
[0005] As already described, the main purpose of cathodically depositable electrocoating materials is corrosion protection of metal substrates. Quite obviously, effective crosslinking and thus film formation is one of the most critical elements to obtain such corrosion protection. Therefore, the presence of a sufficient amount and concentration of a curing catalyst is key.
[0006] However, a major challenge in this regard is that during the conventional use of an electrodeposition coating bath filled with a corresponding electrodeposition coating material composition (i.e., during the coating of a conductive substrate by cathodic electrodeposition coating), the continuous introduction of phosphate species (and poisoning by phosphate species) is almost unavoidable. Quite obviously, the reason is the phosphating pretreatment carried out before the corresponding substrate is immersed in the electrodeposition bath. Phosphates in turn lead to contamination of the catalyst, i.e., the process by which the catalyst is degraded into inactive species that do not have any remaining or at least significantly reduced catalytic activity.
[0007] question
[0008] Therefore, the basic object of the present invention is to provide an electrodeposition coating material which overcomes the above-mentioned technical disadvantages, i.e., it has a high robustness against phosphate contamination. More specifically, the electrodeposition coating material and the corresponding electrodeposition coating bath containing the corresponding electrodeposition coating material composition should show significantly improved resistance against phosphate contamination. Therefore, the electrodeposition coating produced by these baths and compositions, respectively, should be appropriately curable (i.e., crosslinkable), even in the presence of a large amount of phosphate in the bath during production (illustrating phosphate contamination that can be identified in industrial real scenarios).
[0009] plan
[0010] This object has been solved by the subject matter of the claims of the present application and by its preferred embodiments disclosed in the present description, ie by the subject matter described herein.
[0011] The first subject of the present invention is a cathodically depositable aqueous electrodeposition coating material composition comprising
[0012] (I) at least one aqueous binder dispersion comprising at least one cathodically depositable polymer (a) and at least one crosslinker component (b),
[0013] (II) at least one pigment paste containing at least one pigment and / or filler (c) and at least one polymer as grinding resin,
[0014] The composition further comprises at least one type of composite particles (p), the composite particles comprising at least one metal-containing catalyst (pc) and at least one (meth)acrylate-based polymer (mp).
[0015] The above cathodically depositable aqueous electrodeposition coating material composition is also referred to as the electrodeposition coating material composition of the present invention or simply as the composition of the present invention.
[0016] Another subject of the present invention is a method for at least partially coating an electrically conductive substrate by cathodic electrodeposition coating, the method comprising at least steps (1) to (5), namely
[0017] (1) at least partially immersing the conductive substrate in an electrodeposition coating bath containing the electrodeposition coating material composition of the present invention,
[0018] (2) connecting the substrate as a cathode,
[0019] (3) depositing a coating film obtained from the electrodeposition coating material composition on the substrate using direct current,
[0020] (4) removing the coated substrate from the electrodeposition coating bath, and
[0021] (5) Baking the coating film deposited on the substrate.
[0022] Another subject of the present invention is an electrically conductive substrate which is at least partially coated with a baked electrodeposition coating material composition according to the invention and / or is obtainable by a process according to the invention.
[0023] It has been unexpectedly found that the electrodeposition coating material composition of the present invention allows the production of electrocoated substrates that maintain the desired properties of these coatings and substrates, even in the presence of large amounts of phosphates. Thus, the goal of achieving excellent resistance to phosphate staining is achieved by maintaining the excellent characteristic curve of the electrodeposition coating produced under conditions involving relatively high phosphate concentrations. DETAILED DESCRIPTION
[0024] In the sense of the present invention, the term "comprising" in relation to the electrodeposition coating material composition of the present invention, for example, includes but is not limited to the meaning of "consisting of". Thus, for example, with respect to the electrodeposition coating material composition of the present invention, in addition to components (a), (b) and water, the binder dispersion (I) may contain therein one or more additional components specified below and optionally contained in the electrodeposition coating material composition of the present invention. In each case, all components may be present in its preferred embodiment, as specified below. "Consisting of" may also be referred to as "only comprising" or "exclusively comprising", i.e., "comprising" may be referred to as a general term including the specific term "consisting of".
[0025] Electrodeposition coating material composition of the present invention
[0026] The cathodically depositable aqueous electrodeposition coating material composition of the present invention (hereinafter also referred to as the electrodeposition coating material composition of the present invention or the composition of the present invention) comprises at least one binder dispersion (I), the at least one binder dispersion comprising at least one cathodically depositable polymer (a) (also referred to as component (a)) and at least one crosslinking agent (b) (also referred to as component (b)); and at least one pigment paste (II), the at least one pigment paste comprising at least one pigment and / or filler. The composition of the present invention further comprises water. The terms "electrodeposition coating material composition" and "electrodeposition coating composition" used herein are interchangeable.
[0027] The cathodically depositable aqueous electrodeposition coating material composition of the present invention is suitable for at least partially coating a conductive substrate with an electrodeposition coating composition, meaning that it is suitable for at least partially applying to a substrate surface of a conductive substrate and its application results in an electrodeposition coating film on the substrate surface.
[0028] The cathode-depositable electrodeposition coating material composition of the present invention is aqueous. For the purposes of the present invention, the term "aqueous" in relation to the electrodeposition coating material composition of the present invention is preferably understood to mean water, as a solvent and / or as a diluent, as the main component of all solvents and / or diluents present in the electrodeposition coating material composition, preferably in an amount of at least 35 wt.-% based on the total weight of the electrodeposition coating composition of the present invention. Organic solvents may additionally be present in a smaller proportion, preferably in an amount of <20 wt.-%.
[0029] The electrodeposition coating composition according to the invention preferably comprises a water fraction of at least 40 wt.-%, more preferably at least 50 wt.-%, still more preferably at least 60 wt.-%, yet more preferably at least 65 wt.-%, in particular at least 70 wt.-%, most preferably at least 75 wt.-%, in each case based on the total weight of the electrodeposition coating composition.
[0030] The electrodeposition coating composition of the invention preferably comprises an organic solvent fraction of <10 wt.-%, more preferably in the range of 0 to <10 wt.-%, very preferably in the range of 0 to <7.5 wt.-% or 0 to <5 wt.-% or 0 to 2 wt.-%, in each case based on the total weight of the electrodeposition coating composition. Examples of such organic solvents include heterocyclic, aliphatic or aromatic hydrocarbons, monohydric or polyhydric alcohols, in particular methanol and / or ethanol, ethers, esters, ketones and amides, such as, for example, N-methylpyrrolidone, N-ethylpyrrolidone, dimethylformamide, toluene, xylene, butanol, ethylene glycol, propylene glycol and butyl glycol ether and also their acetates, butyl diglycol, diethylene glycol dimethyl ether, cyclohexanone, methyl ethyl ketone, methyl isobutyl ketone, acetone, isophorone, or mixtures thereof. Prominent examples of such organic solvents are, for example, glycol ethers such as butyl glycol or propylene glycol ethers such as butoxypropanol or phenoxypropanol.
[0031] The solid content of the electrodeposition coating material composition of the present invention is preferably in the range of 5 to 35 wt.-%, more preferably 7.5 to 30 wt.-%, very preferably 10 to 27.5 wt.-%, more particularly 12.5 to 25 wt.-%, most preferably 15 to 22.5 wt.-% or 15 to 20 wt.-%, in each case based on the total weight of the electrodeposition coating composition. The solid content, in other words the non-volatile part, is determined according to the method described below.
[0032] The electrodeposition coating material composition of the present invention preferably has a pH in the range of 2.0 to 10.0, more preferably in the range of 2.5 to 9.5 or in the range of 2.5 to 9.0, very preferably in the range of 3.0 to 8.5 or in the range of 3.0 to 8.0, more particularly in the range of 2.5 to 7.5 or in the range of 3.5 to 7.0, especially preferably in the range of 4.0 to 6.5, most preferably in the range of 3.5 to 6.5 or 5.0 to 6.0.
[0033] The electrodeposition coating material of the composition comprises component (a) in an amount preferably in the range of 15 to 85 wt.-%, more preferably 20 to 80 wt.-%, very preferably 25 to 77.5 wt.-%, more particularly 30 to 75 wt.-% or 35 to 75 wt.-%, most preferably 40 to 70 wt.-% or 45 to 70 wt.-% or 50 to 70 wt.-%, in each case based on the total solid content of the electrodeposition coating composition. Alternatively, the electrodeposition coating material composition of the present invention comprises component (a) in an amount preferably in the range of 1 to 80 wt.-%, more preferably 2.5 to 75 wt.-%, very preferably 5 to 70 wt.-%, more particularly 7.5 to 65 wt.-%, most preferably 8 to 60 wt.-% or 10 to 50 wt.-%, in each case based on the total weight of the electrodeposition coating material composition and the coating bath.
[0034] The electrodeposition coating material composition of the present invention further comprises at least one crosslinking agent component (b), which is preferably present in an amount ranging from 5 to 45 wt.%, more preferably from 6 to 42.5 wt.%, very preferably from 7 to 40 wt.%, more particularly from 8 to 37.5 wt.% or from 9 to 35 wt.%, most preferably from 10 to 35 wt.%, particularly preferably from 15 to 35 wt.%, in each case based on the total solid content of the electrodeposition coating composition. Alternatively, the electrodeposition coating composition of the present invention comprises at least one crosslinking agent component (b), which is preferably present in an amount ranging from 0.5 to 30 wt.%, more preferably from 1 to 25 wt.%, very preferably from 1.5 to 20 wt.%, more particularly from 2 to 17.5 wt.%, most preferably from 2.5 to 15 wt.%, particularly preferably from 3 to 10 wt.%, in each case based on the total weight of the electrodeposition coating material composition and the coating bath.
[0035] The fractions in wt.-% of all components (a), (b) and water contained in the electrodeposition coating composition of the invention and also of further components which may be present additionally add up to 100 wt.-%, based on the total weight of the electrodeposition coating material composition.
[0036] The relative weight ratio of components (a) and (b) to each other in the electrodeposition coating material composition is preferably in the range of 5:1 to 1.1:1, more preferably in the range of 4.5:1 to 1.1:1, very preferably in the range of 4:1 to 1.2:1, and more particularly in the range of 3:1 to 1.5:1.
[0037] The composition of the present invention comprises at least one, preferably exactly one, binder dispersion (I). As known to those skilled in the art, electrodeposition coating compositions often contain such binder dispersions, i.e. aqueous dispersions containing at least one polymer as binder. In addition, the composition of the present invention contains at least one pigment paste (II). Again, as known to those skilled in the art, electrodeposition coating compositions often contain such pigment pastes.
[0038] In the following, different essential and optional components of the composition of the present invention are described.More details about the binder dispersion (I) and the pigment paste (II) will also be presented further below.
[0039] Component (a)
[0040] Component (a) is at least one cathodically depositable polymer, which preferably acts as at least one binder in the electrodeposition coating material composition of the present invention. At the same time, component (a) may also act as a grinding resin, as will be outlined in more detail below.
[0041] Any polymer is suitable as binder and thus as component (a) as long as it is cathodically depositable. Preference is given to poly(meth)acrylates, (meth)acrylate copolymers, and epoxide polymers.
[0042] Preferably, component (a) of the electrodeposition coating composition of the present invention comprises and / or is at least one epoxide-amine adduct.
[0043] Epoxide-amine adducts for the purposes of the present invention are the reaction products of at least one epoxy resin and at least one amine. The epoxy-amine adducts are hydroxy-functional, which means that component (a) is preferably hydroxy-functional. The epoxy resins used are more particularly those based on bisphenol A and / or its derivatives. The amines reacting with the epoxy resins are primary and / or secondary amines or their salts and / or salts of tertiary amines.
[0044] At least one epoxide-amine adduct used as component (a) is preferably a cationic, epoxide-based and amine-modified resin. The preparation of such cationic, amine-modified, epoxide-based resins is known and described in, for example, DE 35 18 732, DE 35 18 770, EP 0 004 090, EP 0 012 463, EP 0 961 797 B1 and EP0 505 445 B1. Cationic, epoxide-based, amine-modified resins are understood to be preferably the reaction product of at least one polyepoxide preferably having two or more (e.g. three) epoxy groups and at least one amine, preferably at least one primary amine and / or secondary amine. Particularly preferred polyepoxides are polyglycidyl ethers of polyphenols prepared from polyphenols and epihalohydrins. The polyphenols used can be bisphenol A and / or bisphenol F in particular. Other suitable polyepoxides are polyglycidyl ethers of polyols such as, for example, ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propylene glycol, 1,4-propylene glycol, 1,5-pentanediol, 1,2,6-hexanetriol, glycerol and 2,2-bis(4-hydroxycyclohexyl)propane. The polyepoxides used may also be modified polyepoxides. Modified polyepoxides are to be understood as those polyepoxides in which some of the reactive functional groups have been reacted with at least one modifying compound. Examples of such modifying compounds are as follows:
[0045] i) compounds containing carboxyl groups, such as saturated or unsaturated monocarboxylic acids (e.g. benzoic acid, linseed oil fatty acid, 2-ethylhexanoic acid, versatic acid), aliphatic, cycloaliphatic and / or aromatic dicarboxylic acids of various chain lengths (e.g. adipic acid, sebacic acid, isophthalic acid, or dimer fatty acids), hydroxyalkylcarboxylic acids (e.g. lactic acid, dimethylolpropionic acid), and carboxyl-containing polyesters, or
[0046] ii) compounds containing amino groups, such as diethylamine or ethylhexylamine or diamines with secondary amino groups, for example N,N'-dialkylalkylenediamines, such as dimethylethylenediamine, N,N'-dialkyl-polyoxyalkylenediamines, such as N,N'-dimethylpolyoxypropylenediamine, cyanoalkylated alkylenediamines, such as bis-N,N'-cyanoethylethylenediamine, cyanoalkylated polyoxyalkylenediamines, such as bis-N,N'-cyanoethylpolyoxypropylenediamine, polyaminoamides, such as, for example, tertiary carbonamides, especially diamines (e.g. hexamethylenediamine), amino-terminated reaction products of polycarboxylic acids, especially dimerized fatty acids and monocarboxylic acids, more especially fatty acids, or reaction products of one mole of diaminohexane with two moles of monoglycidyl ethers or monoglycidyl esters, especially glycidyl esters of α-branched fatty acids, such as versatile carbonic acid, or
[0047] iii) compounds containing hydroxyl groups, such as neopentyl glycol, bisethoxylated neopentyl glycol, neopentyl glycol hydroxypivalate, dimethylhydantoin-N,N'-diethanol, hexane-1,6-diol, hexane-2,5-diol, 1,4-bis(hydroxymethyl)cyclohexane, 1,1-isopropylbis(p-phenoxy)-2-propanol, trimethylolpropane, pentaerythritol or amino alcohols, such as triethanolamine, methyldiethanolamine, or hydroxyl-containing alkyl ketimines, such as aminomethylpropane-1,3-diol methylisobutylketimine or tris(hydroxymethyl)aminomethanecyclohexanoneketimine, and also polyglycol ethers, polyester polyols, polyether polyols, polycaprolactone polyols, polycaprolactam polyols of various functionalities and molecular weights, or
[0048] iv) Saturated or unsaturated fatty acid methyl esters which are esterified with the hydroxyl groups of the epoxy resin in the presence of sodium methoxide.
[0049] For example, examples of amines that can be used to prepare component (a) are monoalkylamines and dialkylamines, such as methylamine, ethylamine, propylamine, butylamine, dimethylamine, diethylamine, dipropylamine, methylbutylamine, alkanolamines, such as methylethanolamine or diethanolamine, dialkylaminoalkylamines, such as dimethylaminoethylamine, diethylaminopropylamine or dimethylaminopropylamine. The amines that can be used can also include other functional groups, provided that they do not destroy the reaction of the amine with the epoxy groups of the optionally modified polyepoxide and do not cause gelation of the reaction mixture. Preferably secondary amines are used. The charge required for dilution and electrodeposition in water can be generated by protonation with a water-soluble acid (e.g., boric acid, formic acid, acetic acid, lactic acid, alkylsulfonic acid (e.g., methanesulfonic acid); preferably acetic acid and / or formic acid). Another way to introduce cationic groups into the optionally modified polyepoxide is to react the epoxy groups of the polyepoxide with an amine salt.
[0050] The epoxide-amine adducts which can be used as component (a) are preferably reaction products of epoxy resins based on bisphenol A with primary and / or secondary amines or their salts and / or salts of tertiary amines.
[0051] Component (b)
[0052] At least one crosslinking agent is present in the electrodeposition coating material composition as component (b), which is preferably selected from the group consisting of blocked polyisocyanates, free polyisocyanates, amino resins, and mixtures thereof. The component (b) is different from the component (a).
[0053] The term "blocked polyisocyanate" is known to the skilled person. Blocked polyisocyanates that can be used are polyisocyanates having at least two isocyanate groups (diisocyanates in the case of exactly two isocyanate groups), but preferably having more than two, such as, for example, 3 to 5 isocyanate groups, wherein the isocyanate groups have reacted such that the blocked polyisocyanate formed is stable at room temperature (i.e. at a temperature of 18° C. to 23° C.), in particular with respect to hydroxyl groups and amino groups, such as primary and / or secondary amino groups, but reacts at elevated temperatures, such as, for example, at ≥80° C., ≥110° C., ≥130° C., ≥140° C., ≥150° C., ≥160° C., ≥170° C., or ≥180°, respectively, with conversion and formation of urethane and / or urea bonds.
[0054] In the preparation of blocked polyisocyanates, any desired organic polyisocyanates suitable for crosslinking can be used. The isocyanates used are preferably (hetero)aliphatic, (hetero)alicyclic, (hetero)aromatic or (hetero)aliphatic-(hetero)aromatic isocyanates. Preferred polyisocyanates are those containing 2 to 36, in particular 6 to 15, carbon atoms. Preferred examples are ethylene 1,2-ethylene diisocyanate, tetramethylene 1,4-diisocyanate, hexamethylene 1,6-diisocyanate (HDI), 2,2,4- and (2,4,4)-trimethylhexamethylene 1,6-diisocyanate (TMDI), diphenylmethane diisocyanate (MDI), 1,9-diisocyanato-5-methylnonane, 1,8-diisocyanato-2,4-dimethyloctane, dodecane 1,12-diisocyanate, ω,ω'-diisocyanatodipropyl ether, cyclobutylene 1,3-diisocyanate, cyclohexane 1,3- and 1,4-diisocyanate, 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate (isophorone diisocyanate). isocyanate, IPDI), 1,4-diisocyanatomethyl-2,3,5,6-tetramethyl-cyclohexane, decahydro-8-methyl (1,4-naphthalene-2 (or 3), 5-dimethyl diisocyanate, hexahydro-4,7-indane-1 (or 2), 5 (or 6)-dimethyl diisocyanate, hexahydro-4,7-indane-1 (or 2), 5 (or 6)-dimethyl diisocyanate, hexahydro-4,7-indane-1 (or 2), 5 (or 6)-dimethyl diisocyanate, hexahydrotoluene 2,4- and / or 2,6-diisocyanate (H6-TDI), toluene 2,4- and / or 2,6-diisocyanate (TDI), perhydrodiphenylmethane 2,4′-diisocyanate, perhydrodiphenylmethane 4,4′-diisocyanate (H 124-Diisocyanatomethyl)-2,3-diisocyanatobutane, 1,10-diisocyanatodecane, 1,5-diisocyanatohexane, 1,3-diisocyanatomethylcyclohexane, 1,4-diisocyanatomethylcyclohexane, 2,5(2,6)-bis(isocyanatomethyl)bicyclo[2.2.1]heptane (NBDI), and also any mixtures of these compounds. It is also possible to use polyisocyanates having a higher isocyanate functionality. Examples thereof are trimerized hexamethylene diisocyanate and trimerized isophorone diisocyanate, more particularly the corresponding isocyanurates. Furthermore, it is also possible to use mixtures of polyisocyanates.
[0055] For the end-capping of polyisocyanates, any desired suitable aliphatic, alicyclic or aromatic alkyl monoalcohols can be preferably used. Examples thereof are aliphatic alcohols such as methanol, ethanol, chloroethanol, propanol, butanol, pentanol, hexanol, heptanol, octanol, nonanol, 3,3,5-trimethylhexanol, decanol and lauryl alcohol; alicyclic alcohols such as cyclopentanol and cyclohexanol; aromatic alkyl alcohols such as benzyl alcohol and methylbenzyl alcohol. Similarly, suitable diols such as ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol and / or polyols can also be used for the end-capping of polyisocyanates. Other suitable end-capping agents are hydroxylamines such as ethanolamine, oximes such as methyl ethyl ketone oxime, acetone oxime and cyclohexanone oxime, and amines such as dibutylamine and diisopropylamine.
[0056] Tris (alkoxycarbonylamino) -1,3,5-triazines (TACT) are likewise known to the skilled person. It is known to use tris (alkoxycarbonylamino) -1,3,5-triazines as crosslinking agents in coating material compositions. For example, DE 197 12940A1 describes the use of such crosslinking agents in primer materials. U.S. Pat. No. 5,084,541 describes the preparation of corresponding compounds that can be used as component (c). For the purposes of the present invention, such triazines are covered by the term "blocked polyisocyanates".
[0057] Amino resins (amino plastic resins) are also known to the skilled person. The amino resin used is preferably a melamine resin, more particularly a melamine-formaldehyde resin, which is also known to the skilled person. However, preference is given to not using amino resins such as melamine-formaldehyde resins as crosslinking agents (b). Therefore, the electrodeposition coating material composition of the present invention preferably does not contain amino resins such as melamine-formaldehyde resins.
[0058] The electrodeposition coating material composition of the present invention is preferably used as a one-component (1K) coating composition. For this reason, the electrodeposition coating composition of the present invention preferably does not contain free polyisocyanate.
[0059] Most preferably, at least one component (b) of the composition of the present invention is selected from blocked polyisocyanates. Preferred blocked polyisocyanates have, for example, an NCO content of 200 to 300 g / eq, more preferably 225 to 275 g / eq (wherein g / eq means grams of NCO component per mol of the component).
[0060] The molar ratio of hydroxyl groups of component (a) to NCO groups of component (b) is preferably from 1.5 to 3.5, preferably from 2.0 to 3.0.
[0061] Pigments and / or fillers (c)
[0062] The electrodeposition coating material composition of the present invention comprises at least one pigment and / or at least one filler (c).
[0063] The term "pigment" is known to the skilled person, for example from DIN 55943 (date: October 2001). "Pigment" in the sense of the present invention preferably refers to components in the form of powders or flakes, which are substantially, preferably completely insoluble in the medium surrounding them, such as, for example, the electrodeposition coating material composition of the present invention. Pigments are preferably colorants and / or substances which can act as pigments due to their magnetic, electric and / or electromagnetic properties. Pigments differ from "fillers" preferably in their refractive index, the refractive index of pigments being ≥1.7.
[0064] The term "filler" is known to the skilled person, for example from DIN 55943 (date: October 2001). For the purposes of the present invention, a "filler" is preferably a component which is substantially, preferably completely, insoluble in the application medium (such as, for example, the electrodeposition coating material composition of the present invention) and which is used in particular to increase the volume. "Fillers" in the sense of the present invention differ from "pigments" preferably in their refractive index, the refractive index of fillers being <1.7.
[0065] Any conventional pigment known to the technician can be used. Examples of suitable pigments are inorganic and organic coloring pigments. Examples of suitable inorganic coloring pigments are white pigments, such as titanium dioxide, zinc white, zinc sulfide or zinc lithopone; black pigments, such as carbon black, iron manganese black or spinel black; colored pigments, such as chromium oxide, hydrated chromium oxide green, cobalt green or ultramarine green, cobalt blue, ultramarine blue or manganese blue, ultramarine violet or cobalt violet and manganese violet, iron oxide red, cadmium sulfoselenide, molybdenum chromium red or ultramarine red; iron oxide brown, mixed brown, spinel phase and corundum phase or chrome orange; or iron oxide yellow, nickel titanium yellow, chrome titanium yellow, cadmium sulfide, cadmium sulfide zinc, chrome yellow or bismuth vanadate. Other inorganic coloring pigments are silicon dioxide, aluminum oxide, hydrated aluminum oxide, especially boehmite, titanium dioxide, zirconium oxide, cerium oxide, and mixtures thereof. Examples of suitable organic colored pigments are monoazo pigments, disazo pigments, anthraquinone pigments, benzimidazole pigments, quinacridone pigments, quinophthalone pigments, diketopyrrolopyrrole pigments, dioxazine pigments, indanthrone pigments, isoindoline pigments, isoindolinone pigments, azomethine pigments, thioindigo pigments, metal complex pigments, perinone pigments, perylene pigments, phthalocyanine pigments or aniline black.
[0066] Any conventional filler known to the skilled person can be used. Examples of suitable fillers are kaolin, dolomite, calcite, chalk, calcium sulfate, barium sulfate, graphite, silicates such as magnesium silicate, especially corresponding phyllosilicates such as hectorite, bentonite, montmorillonite, talc and / or mica, silicon dioxide, especially fumed silica, hydroxides such as aluminum hydroxide or magnesium hydroxide. As examples of kaolin, mention may be made of commercial products like ASP 200 (non-calcined kaolin, BASF) or KaMin 2000C (calcined kaolin, KaMin) (preferably ASP 200). In addition, organic fillers such as textile fibers, cellulose fibers, polyethylene fibers or polymer powders can be applied. For further details, reference is made to Lexikon Lacke und Druckfarben, Georg Thieme Verlag, 1998, pp. 250 ff., “Fillers”.
[0067] Based on the total weight of the electrodeposition material coating composition of the present invention, the pigment plus filler content is preferably in the range of 0.1 to 20.0 wt.-%, more preferably 0.1 to 15.0 wt.-%, very preferably 0.1 to 10.0 wt.-%, especially preferably 0.1 to 5.0 wt.-%, and more particularly 0.1 to 2.5 wt.-%.
[0068] Pigments and / or fillers are incorporated into the electrodeposition coating material composition in the form of a pigment paste (II). It is possible and preferred that a pigment paste (II) contains both one or more pigments and / or fillers. Such pastes typically contain at least one polymer used as a grinding resin. Preferably, therefore, at least one such polymer used as a grinding resin is contained in the electrodeposition coating composition of the present invention. It is possible that at least one polymer (a) used as a binder in the electrodeposition coating material composition can also additionally serve as a grinding resin in the pigment paste (II). The grinding resin in question is preferably an epoxide-amine adduct, as outlined above, which can correspond to and / or can be included under the definition of component (a). The polymer used as a grinding resin preferably has a structural unit that interacts with the surface of the pigment. Therefore, the grinding resin preferably has the effect of an emulsifier. In many cases, quaternary ammonium compounds are incorporated for the purpose of improving the properties of the grinding resin. In addition to the grinding resin, additional conventional additives such as wetting agents or dispersants (such as the optional component (d) described below) and also solvents (water and organic co-solvents) can also be contained. The production of the pigment paste includes a grinding / milling step. Thus, pigment and / or filler are preferably ground together with grinding resin and other components / solvent to form pigment paste. In order to produce final electrodeposition coating material composition, this paste is mixed with remaining ingredients, particularly binder dispersion (I). The use of pigment paste advantageously leads to greater flexibility in electrodeposition coating, because the pigment / filler and binder of electrodeposition coating material composition can easily adapt to practical requirements at any time via the amount of pigment paste.
[0069] As mentioned above, composition of the present invention comprises at least one adhesive dispersion (I). Adhesive dispersion (I) contains at least one component (a) and at least one component (b). In addition, adhesive dispersion (I) conventionally contains the other optional component (d) mentioned below. Except water, also having other organic cosolvent can be a part of adhesive dispersion (I).
[0070] Additional optional ingredients
[0071] Depending on the desired application, the electrodeposition coating material composition of the present invention may include one or more commonly used additional additives as one or more optional components (d). Component (d) is different from any one of components (a) to (c) and is also different from the composite particles (p) described below. Preferably, these additives are selected from the group consisting of: wetting agents, emulsifiers, dispersants, surface active compounds such as surfactants, flow control aids, solubilizers, defoamers, rheological aids, antioxidants, stabilizers (preferably heat stabilizers), process stabilizers, and UV and / or light stabilizers, tougheners, plasticizers, and mixtures of the above additives. The additive content can vary very widely depending on the intended use. Based on the gross weight of the electrodeposition material coating composition of the present invention, the additive content is preferably in the range of 0.1 to 20.0 wt.-%, more preferably 0.1 to 15.0 wt.-%, very preferably 0.1 to 10.0 wt.-%, especially preferably 0.1 to 5.0 wt.-%, and more particularly 0.1 to 2.5 wt.-%.
[0072] Composite particles (p)
[0073] The composition of the present invention comprises at least one type of composite particles (p) as an essential component. Preferably, exactly one type of composite particles is comprised. The composite particles (p) comprise at least one metal-containing catalyst (pc), preferably exactly one metal-containing catalyst (pc). Quite obviously, the metal-containing catalyst (pc) is a metal-containing catalyst for catalyzing the chemical reaction of the cathodically depositable polymer (a) and the crosslinker component (b).
[0074] The metal-containing catalyst (pc) is particularly selected from catalysts containing tin or bismuth. Even more preferably, the catalyst (pc) is a bismuth-containing catalyst, in particular a bismuth (III)-containing catalyst. Particularly preferably, a bismuth-containing catalyst can be used, such as bismuth (III) oxide, basic bismuth oxide (III), bismuth (III) hydroxide, bismuth (III) carbonate, bismuth (III) nitrate, bismuth (III) subnitrate (basic bismuth (III) nitrate), bismuth (III) salicylate and / or bismuth (III) subsalicylate (basic bismuth (III) salicylate), bismuth (III) carboxylates, in particular bismuth (III) neodecanoate, and also mixtures thereof. Particularly preferred are water-insoluble catalysts, preferably water-insoluble bismuth-containing catalysts. More particularly preferred are bismuth (III) carboxylates, more preferably bismuth (III) neodecanoate.
[0075] The electrodeposition coating material composition of the present invention preferably comprises at least one bismuth (III)-containing catalyst in an amount such that the bismuth (III) content calculated as bismuth metal based on the total weight of the electrodeposition coating material of the present invention is in the range of 10 ppm to 20,000 ppm, preferably 100 to 15,000 ppm, more preferably 500 to 10,000 ppm and particularly preferably 1000 to 5000 ppm. The amount of bismuth calculated as metal can be determined by inductively coupled plasma-atomic emission spectrometry (ICP-OES) according to DIN EN ISO 11885 (date: September 2009). Therefore, the amount of composite particles (p) is preferably selected to correspond to the bismuth amount (calculated as metal) specified above.
[0076] The composite particles (p) comprise at least one (meth)acrylate-based polymer (mp), preferably exactly one such polymer (mp).
[0077] In general, polymers based on (meth)acrylates are known to those skilled in the art. Such polymers include monomers based on acrylates and / or based on methacrylates in a reactive form, such as esters, nitrile or amides of (meth)acrylic acid and (meth)acrylic acid. Of course, polymers based on (meth)acrylates can also contain other ethylenically unsaturated monomers in a reactive form, such as vinyl ethylenically unsaturated monomers, α-β unsaturated carboxylic acids and allyl compounds. Therefore, although a significant portion of the monomers, i.e., greater than 30% by weight or greater than 50% by weight (in each case based on the total weight of the monomers) will be monomers based on acrylates and / or based on methacrylates in any case, such polymers can also include the above-mentioned other ethylenically unsaturated monomers. Such ethylenically unsaturated monomers can be monoolefinic or polyolefinically unsaturated. The production of these polymers includes, for example, free radical polymerization of the mentioned ethylenically unsaturated monomers.
[0078] The (meth)acrylate-based monoethylenically unsaturated monomer may be, for example, (meth)acrylic acid and (meth)acrylic acid esters, nitriles, or amides.
[0079] Esters of (meth)acrylic acid are in particular those which have groups R which are not ethylenically unsaturated.
[0080]
[0081] The group R may be aliphatic or aromatic. The group R is preferably aliphatic. The group R may be, for example, an alkyl group, or may contain heteroatoms. An example of a group R containing heteroatoms is an ether. Preference is given to using at least, but not necessarily only, monomers in which the group R is an alkyl group.
[0082] If R is an alkyl group, it may be a linear, branched or cyclic alkyl group. In all three cases, the group in question may be unsubstituted or substituted by a functional group. The alkyl group preferably has 1 to 24, more preferably 1 to 10 carbon atoms.
[0083] Particularly preferred suitable monounsaturated (meth)acrylic acid esters with unsubstituted alkyl groups are methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, ethylhexyl (meth)acrylate, propylheptyl (meth)acrylate, 3,3,5-trimethylhexyl (meth)acrylate, stearyl (meth)acrylate, lauryl (meth)acrylate, cycloalkyl (meth)acrylates such as cyclopentyl (meth)acrylate, isobornyl (meth)acrylate and also cyclohexyl (meth)acrylate, with n-butyl (meth)acrylate and tert-butyl (meth)acrylate and methyl methacrylate being particularly preferred.
[0084] Suitable monounsaturated esters of (meth)acrylic acid having substituted alkyl groups may be substituted with one or more hydroxyl groups, phosphate groups or amino groups (such as primary, secondary or tertiary amino groups).
[0085] The monounsaturated esters of (meth)acrylic acid having an alkyl group substituted by one or more hydroxyl groups are 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate, among which 2-hydroxyethyl (meth)acrylate is particularly preferred.
[0086] The monounsaturated ester of (meth)acrylic acid having a phosphate group is, for example, the phosphate ester of polypropylene glycol monomethacrylate, such as Sipomer PAM 200 commercially available from Rhodia.
[0087] The monosaturated ester of (meth)acrylic acid having an amino group is, for example, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylate, diethylaminopropyl (meth)acrylate, 2-(tert-butylamino)ethyl (meth)acrylate, 2-aminoethyl (meth)acrylate hydrochloride, 2-N-morpholinoethyl (meth)acrylate, 2-(diisopropylamino)ethyl (meth)acrylate or 3-(diisopropylamino)propyl (meth)acrylate.
[0088] Amides of (meth)acrylic acid are those known to the person skilled in the art, for example (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-propyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-butyl(meth)acrylamide, N-tert-butyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-propyl(meth)acrylamide, N-butyl(meth)acrylamide, N-phenyl(meth)acrylamide, N-(1-naphthyl)-N-phenyl(meth)acrylamide, N-(triphenylmethyl)methacrylamide, N-[3-(dimethylamino)-propyl]-(meth)acrylamide, N-[3-(diethylamino)-propyl]-(meth)acrylamide, Acrylamide, N-[2-(dimethylamino)-ethyl]-(meth)acrylamide, N-[2-(diethylamino)-ethyl]-(meth)acrylamide, 4-(meth)acryloylmorpholine, N-(3-aminopropyl) (meth)acrylamide hydrochloride, N-(2-aminoethyl)-(meth)acrylamide hydrochloride, diacetone (meth)acrylamide, N-(hydroxymethyl)-(meth)acrylamide, N-(hydroxyethyl)-(meth)acrylamide, N-(isobutoxymethyl) (meth)acrylamide, N-(hydroxyethyl)-(meth)acrylamide, N-(3-methoxypropyl) (meth)acrylamide, 2-hydroxypropyl (meth)acrylamide, N-[tris (hydroxymethyl) methyl] acrylamide or N-hydroxymethyl (meth)acrylamide.
[0089] The ethylenically monounsaturated monomer may be a monomer having a non-ethylenically unsaturated group R' on the vinyl group.
[0090]
[0091] The group R' may be aliphatic or aromatic, with aromatic groups being preferred.
[0092] The group R' can be a hydrocarbon group or can contain heteroatoms. Examples of heteroatom-containing groups R' are ethers, esters, amides, nitrile and heterocycles. The group R' is preferably a hydrocarbon group. When R' is a hydrocarbon group, it can be unsubstituted or substituted with heteroatoms, wherein unsubstituted groups are preferred. The group R' is preferably an aromatic hydrocarbon group.
[0093] Preferred vinylethylenically unsaturated monomers are vinylaromatic hydrocarbons, especially vinyltoluene, α-methylstyrene and especially styrene.
[0094] If heteroatoms are present, ethylenically unsaturated monomers are preferred, such as acrylonitrile, methacrylonitrile, acrylamide, methacrylamide, N,N-dimethylacrylamide, N-[3-(dimethylamino)-propyl]-methacrylamide, vinyl acetate, vinyl propionate, vinyl chloride, N-vinylpyrrolidone, N-vinylcaprolactam, N-vinylformamide, N-vinylimidazole and N-vinyl-2-methylimidazoline.
[0095] Examples of suitable polyethylenically unsaturated monomers include esters of (meth)acrylic acid having an ethylenically unsaturated group R″, and allyl ethers of monohydric or polyhydric alcohols. The group R″ may be an allyl group or a (meth)acryloyl group.
[0096]
[0097] Preferred multiethylenically unsaturated monomers include ethylene glycol di(meth)acrylate, 1,2-propylene glycol di(meth)acrylate, 2,2-propylene glycol di(meth)acrylate, butane-1,4-diol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 3-methylpentanediol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, and allyl (meth)acrylate.
[0098] Polyethylenically unsaturated compounds further include acrylates and methacrylates of alcohols having more than two OH groups, such as, for example, trimethylolpropane tri(meth)acrylate or glycerol tri(meth)acrylate, but also trimethylolpropane di(meth)acrylate monoallyl ether, trimethylolpropane (meth)acrylate diallyl ether, pentaerythritol tri(meth)acrylate monoallyl ether, pentaerythritol di(meth)acrylate diallyl ether, pentaerythritol (meth)acrylate triallyl ether, triallyl sucrose and pentaallyl sucrose.
[0099] Preferably, the (meth)acrylate-based polymer comprises a monomer mixture consisting of: (a) 40 to 98% by weight, preferably 50 to 88% by weight, of C (meth)acrylic acid; 1 -C 10-alkyl esters, (b) 2 to 45% by weight, preferably 5 to 30% by weight, of polyethylenically unsaturated monomers, in particular diethylenically unsaturated monomers, and (c) 0 to 20% by weight, preferably 2 to 10% by weight, of monoethylenically unsaturated monomers other than monomer (a). The term "polymer consisting of a monomer mixture consisting of..." is equivalent to the term "polymer made (ie polymerized)". Preferably, the (meth)acrylate-based polymer consists of the aforementioned monomer mixture.
[0100] In a preferred embodiment, at least one monomer (c) is selected from monomers having at least one, preferably one, amino group. Even more preferably, monomer (c) is selected from at least one monomer having at least one, preferably one, amino group (i.e. monomer (c) consists only of monomers having at least one, preferably one, amino group). The reason is that such monomers can be protonated and thus converted into a cationic state, which means that during cationic electrodeposition, the composite particles can be driven onto the substrate to be coated in order to facilitate the actual deposition (similar to what occurs with component (a) above).
[0101] Preferably, the (meth)acrylate-based polymer is prepared in the presence of a metal-containing catalyst. Such in situ production provides very well for the formation of actual composite particles, ie particles that are a hybrid of both (meth)acrylate-based polymer and catalyst.
[0102] Therefore, the production principle of composite particles is preferably based on the production of the above specified monomers and catalysts together with preferably free radical initiators in the reaction medium for polymerizing the monomers. Preferably, the production is carried out in an oil-in-water emulsion, wherein the monomers and the preferred water-insoluble catalyst and the organic solvent (such as n-butyl acetate) potentially used for solubilizing the catalyst are in the form of dispersed phase in the aqueous dispersion medium, thus preferably comprising a dispersant to enhance the formation of dispersion characteristics and avoid the aggregation and coagulation of the formed particles. In a preferred embodiment, the addition of the free radical initiator can be delayed until after the dispersion process. Then by, for example, heating the polymerization of the monomers, and optionally by further temperature increase to control the polymerization of the monomers, thus the resulting polymer and the catalyst form composite particles. Of course, polymerization can also be induced by other known means (such as redox initiators or UV radiation). However, temperature increase is preferred. Finally, in this embodiment, the composite particles will be obtained in the form of an aqueous dispersion (or emulsion), that is, in the form of particles present in an aqueous medium. Preferably, the composite particles (p) exist in the form of an aqueous dispersion after production, because this allows direct application in the electrocoating material of the present invention.
[0103] As mentioned above, the production of the particles is preferably carried out in the presence of at least one dispersant. Therefore, the aqueous phase generally contains at least one dispersant in order to stabilize the droplets of the o / w emulsion during its production. Dispersants suitable for stabilizing oil / water emulsions are common knowledge and are mentioned, for example, in EP 2794085 and EP 3007815 (also referred to therein as protective colloids), the teachings of which are expressly incorporated by reference. Typical dispersants include polysaccharides, polyvinyl alcohol, polymers with sulfonate groups, polymers with carboxylate groups, polyvinyl pyrrolidone, copolymers of vinyl pyrrolidone and inorganic Pickering stabilizers. Suitable dispersants are typically water-soluble organic polymers. Inorganic Pickering systems (such as colloidal silica and colloidal clay minerals) can also be used as dispersants for this purpose. Pickering stabilizers (also referred to as Pickering systems) can be used as is or in combination with water-soluble organic polymers. Dispersants from the group of polysaccharides include, for example, cellulose derivatives such as hydroxyethylcellulose, methylhydroxyethylcellulose, methylcellulose and carboxymethylcellulose, methylhydroxypropylcellulose, lignin sulfonates and also mixtures thereof.
[0104] Among the organic water-soluble polymers, particularly preferred are partially hydrolyzed polyvinyl acetates, also referred to as partially hydrolyzed polyvinyl alcohols (PVA), wherein in particular there is a degree of hydrolysis of 70% to 99.9%, in particular 75% to 99%, more particularly 80% to 95%. In addition, PVA copolymers are also suitable as described in WO 2015 / 165836. PVA may in particular be a carboxyl-modified anionic PVA. Such a carboxyl-modified PVA preferably has a carboxyl ratio of 1 to 6 mol%. In particular, the carboxyl-modified PVA is used as a dispersant, and its 4% by weight aqueous solution preferably has a viscosity in the range of 20.0 to 30.0 mPa*s at 20°C. In the group of partially hydrolyzed polyvinyl alcohols, particularly preferred are those having a degree of hydrolysis of 70% to 99.9%, in particular 75% to 99%, more particularly 80% to 95%, and especially 85% to 95%. Particularly preferred dispersants are carboxyl-modified anionic PVAs having 1 to 6 mol% of carboxyl groups based on the amount of repeating units and a degree of hydrolysis in the range of 75% to 99%, particularly 80% to 95% and especially 85% to 95%. Among these, preferred are those whose 4% by weight aqueous solution has a viscosity of 20.0 to 30.0 mPa*s at 20°C.
[0105] Also preferred dispersants are salt polymers with sulfonate groups. Such polymers include homopolymers and copolymers of ethylenically unsaturated sulfonic acids (such as 2-acrylamide-2-methylpropane sulfonic acid) optionally with one or more water-soluble monomers (such as acrylamide or methacrylamide and salts thereof). They also include salts of lignin-based sulfonic acids, also referred to as lignin sulfonates (lignin sulfonate or lignosulfonate). Suitable lignin sulfonates can include, for example, sodium lignin sulfonate, calcium lignin sulfonate, ammonium lignin sulfonate, magnesium lignin sulfonate, potassium lignin sulfonate or sulfomethylated lignin sulfonates. The above-mentioned salts are particularly sodium salts or ammonium salts of polymers with sulfonate groups.
[0106] Among the organic water-soluble polymers, preference is also given to polymers with carboxyl groups. Typically, such polymers are homopolymers or copolymers of monoethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, maleic acid, fumaric acid or itaconic acid. The polymers with carboxyl groups are typically used in their partially or completely neutralized form, wherein the carboxyl groups are converted in the form of anionic carboxylates. Typically, the counterion is selected from sodium and ammonium.
[0107] General production processes for such composite particles are generally described by way of example in DE-A-10139 171 and in applications WO 2011 / 004006, US 2015 / 361227 A1 and WO 2012 / 110443, which are expressly incorporated herein by reference.
[0108] Without wishing to be bound by a certain theory, it is expected that the above-described production process carried out in an oil-in-water emulsion facilitates the formation of capsules, i.e. particles having a shell or wall essentially comprising the resulting (meth)acrylate-based polymer (mp), which encloses a preferably water-insoluble catalyst (pc), which, moreover, is preferably dissolved in an organic solvent.
[0109] The composite particles preferably have a diameter in the range of 0.2 to 10 μm, preferably 0.5 to 5 μm, in particular 0.5 to 3 μm (d 50 ) in the range of particle size (measured by laser diffraction d 50 (volume-based)). Quite obviously, the particle size given relates to the particle size as measured in the form in which the particles exist after production, ie therefore preferably in the form of an aqueous dispersion (or emulsion).
[0110] The weight ratio (w / w) of the metal-containing catalyst to the (meth)acrylate-based polymer is preferably 98:2 to 20:80, more preferably 97:3 to 50:50 and most preferably 95:5 to 60:40. The weight ratio is calculated by taking into account the total weight of the monomers applied to produce the polymer and the weight of the applied metal catalyst. In addition, preferably, the weight ratio (w / w) of the metal in the metal-containing catalyst (i.e. calculated as metal) to the (meth)acrylate-based polymer is 90:10 to 5:95, more preferably 85:15 to 15:85 and most preferably 80:20 to 20:80.
[0111] The composite particles (p) can be introduced into the composition of the invention by common means. For example, the composite particles (and the aqueous dispersion (emulsion) of particles, respectively) can be applied as a separate formulation component in the production of the composition as is. In addition, the particles (and the aqueous dispersion (emulsion) of particles, respectively) can be part of, for example, the adhesive dispersion (I).
[0112] In line with the above, the present invention also relates to a method for producing composite particles (p) comprising at least one metal-containing catalyst (pc) and at least one (meth)acrylate polymer (mp), wherein the polymer (mp) is prepared in the presence of the metal-containing catalyst (pc), whereby the method comprises the following steps
[0113] (1) preparing an oil-in-water emulsion in which the monomers and the metal-containing catalyst for producing the polymer (mp) are part of or are a dispersed phase in an aqueous medium,
[0114] (2) polymerizing the monomers in the oil-in-water emulsion of step (1) by an initiator.
[0115] Preferably, the oil-in-water emulsion of step (1) comprises at least one protective colloid.
[0116] Furthermore, the invention relates to composite particles (p) produced according to the process defined above.
[0117] The present invention also relates to a method for producing a cathode-depositable electrodeposition coating material composition, the method comprising
[0118] - providing (I) at least one binder dispersion comprising at least one cathodically depositable polymer (a) and at least one crosslinker (b),
[0119] - providing at least one pigment paste (II) comprising at least one pigment and / or filler and at least one grinding resin,
[0120] - optionally providing further components different from components (I) and (II),
[0121] - mixing the binder dispersion (I), the pigment paste (II) and any further potential components of the composition,
[0122] At least one component comprises at least one type of composite particles (p), the composite particles comprising at least one metal-containing catalyst (pc) and at least one (meth)acrylate-based polymer (mp), wherein the polymer (mp) is prepared in the presence of the metal-containing catalyst (pc).
[0123] Quite obviously, any and all essential and also preferred features and embodiments mentioned above in the context of the composition of the invention apply equally to the kit parts and the method of manufacture.
[0124] Method for electrocoating
[0125] Another subject of the present invention is a method for at least partially coating an electrically conductive substrate by cathodic electrodeposition coating, the method comprising at least steps (1) to (5), namely
[0126] (1) at least partially immersing the conductive substrate in an electrodeposition coating bath containing the electrodeposition coating material composition of the present invention,
[0127] (2) connecting the substrate as a cathode,
[0128] (3) depositing a coating film obtained from the electrodeposition coating material composition on the substrate using direct current,
[0129] (4) removing the coated substrate from the electrodeposition coating bath, and
[0130] (5) Baking the coating film deposited on the substrate.
[0131] All preferred embodiments described hereinabove with respect to the electrodeposition coating material composition of the present invention are also preferred embodiments with respect to the above-described method of the present invention for at least partially coating a conductive substrate by cathodic electrodeposition coating using such an electrodeposition coating material composition.
[0132] Preferably, the above method comprises a step (4.1) of rinsing the coated substrate, for example with DI water, between steps (4) and (5). Quite obviously, this step serves to clean the substrate, ie to remove residual coating material that was not well deposited on the substrate.
[0133] The method of the present invention is particularly suitable for the electrodeposition coating of automobile bodies or parts thereof (including corresponding metal substrates). Therefore, preferred substrates are automobile bodies or parts thereof. In particular, such substrates are metal automobile component parts, such as, for example, transverse control arms, spring-loaded control arms or dampers. Such component parts can be cast iron parts or can also be produced by other established methods known in the art. In addition, such substrates are metal automobile bodies, such as automobile bodies that are partially stamped to cut out specific parts or form specific geometric shapes and therefore also include considerable edges.
[0134] Suitable as conductive substrates for use according to the invention are all conductive substrates commonly used and known to the skilled person. The conductive substrate used according to the invention is preferably a metal substrate, more preferably selected from the group consisting of steel, preferably steel selected from the group consisting of bare steel, cold rolled steel (CRS), hot rolled steel, galvanized steel (such as hot dip galvanized steel (HDG)), alloy galvanized steel (e.g. Galvalume, Galvannealed or Galfan) and aluminized steel, aluminum and magnesium, and also Zn / Mg alloys and Zn / Ni alloys. Particularly suitable substrates are parts for the production of car bodies or entire car bodies.
[0135] Before the corresponding electrically conductive substrate is used in step (1) of the method according to the invention, it is preferably cleaned and / or degreased.
[0136] The conductive substrate used according to the invention is preferably a pretreated substrate, for example with at least one metal phosphate such as zinc phosphate. This pretreatment by phosphating is usually carried out after the substrate has been cleaned and before the substrate is coated by electrodeposition in step (1), and is in particular a pretreatment step commonly used in the automotive industry. However, pretreatment methods other than phosphating are also possible, for example thin film pretreatment based on zirconium oxide or typical silanes.
[0137] During the steps (1), (2) and (3) of the method of the present invention, the electrodeposition coating material composition of the present invention is cathode deposited on the substrate area immersed in the bath in step (1). In step (2), the substrate is connected as a cathode, and a voltage is applied between the substrate and at least one counter electrode, which is located in the deposition bath or exists separately from it, for example, through an anion exchange membrane permeable to anions. Therefore, the counter electrode acts as an anode. When an electric current is passed between the anode and the cathode, a firmly adhered coating film is deposited on the cathode, that is, on the immersed part of the substrate. The voltage applied here is preferably in the range of 50 to 500 volts. When the steps (1), (2) and (3) of the method of the present invention are carried out, the electrodeposition coating bath preferably has a bath temperature in the range of 20° C. to 45° C.
[0138] The baking temperature in step (5) is preferably in the range of 100°C to 210°C, more preferably 120°C to 205°C, very preferably 120°C to 200°C, more particularly 125°C to 195°C or 125°C to 190°C, most preferably 130°C to 185°C or 140°C to 180°C.
[0139] After carrying out step (5) of the method of the present invention, one or more additional coatings may be applied to the baked coating film obtained after step (5). For example, a primer and / or filler may be applied, followed by a basecoat and a clearcoat.
[0140] Therefore, the method of the present invention preferably comprises at least one further step (6), namely
[0141] (6) At least one additional coating material composition different from the composition applied in step (1) is at least partially applied to the baked coating film obtained after step (5).
[0142] Substrate
[0143] Another subject of the invention is an electrically conductive substrate at least partially coated with the baked electrodeposition coating material of the invention. The baked coating material corresponds to the baked coating film obtained after step (5) of the process of the invention.
[0144] All preferred embodiments described above with respect to the electrodeposition coating material composition of the invention and the method of the invention are also preferred embodiments with respect to the above-mentioned at least partially coated substrate of the invention.
[0145] Of course, the baked electrodeposition coating produced from the electrodeposition coating material composition of the present invention is also a subject of the present invention.
[0146] use
[0147] Another subject of the present invention is the use of the composite particles (p) for increasing the robustness of electrodeposition coating baths with respect to phosphate contamination.
[0148] method
[0149] 1. Determination of the non-volatile fraction
[0150] The non-volatile fraction (solids or solids content) is determined according to DIN EN ISO 3251 (date: June 2019). This involves weighing 1 g of sample into an aluminum pan that has been dried beforehand, drying the pan with the sample at 180° C. in a drying cabinet for 30 minutes, cooling it in a desiccator and then reweighing. The residue corresponds to the non-volatile fraction (in % or wt.-%) relative to the total amount of sample used.
[0151] 2. Glass transition temperature T g Determination
[0152] The glass transition temperature T was determined by differential scanning calorimetry (DSC) according to DIN 53765:1994-03 using a heating rate of 10 K / min. g .
[0153] 3. Determination of pH value
[0154] The pH value was determined according to DIN 55659-1 (January 2012).
[0155] 4. Determination of dry film thickness
[0156] The film thickness was determined according to DIN EN ISO 2808 (date: May 2007), method 12A using a Dualscope FM40 instrument from Fischer.
[0157] 5. Determination of acetone resistance
[0158] On test plate (GB 6800 / OC Chemetall), carry out the determination of acetone resistance, and this test plate carries out ED coating and solidification according to the 5 step procedures mentioned above.Rubbing the coated plate with hammer-shaped tool, this hammer-shaped tool has the weight of 1kg and the head containing the cotton wool immersed in acetone.Without any additional pressure, hammer-shaped tool and the wool with acetone are pushed and pulled on the coating surface, and push and pull once in each direction is recorded as 1 double friction.200 double frictions are evaluated as excellent acetone resistance, which means that 200 double frictions are the maximum number of double frictions carried out in this test.The double friction number of times provided below in the result part corresponds to the number of times when observing the delamination of the cured coating material (or, when the result is 200 times of acetone resistance, this delamination does not occur).
[0159] 6. Average particle diameter
[0160] The particle size distribution of the composite particles was measured by laser diffraction according to ISO 13320 EN: 2020-01. A Malvern Mastersizer 2000 was used. The data were processed according to the Mie-Theory by software using the "General Model" provided by Malvern Instruments. The important parameters are usually d n Values, for example, where n = 10, 50 and 90, that is, d 10 ,d 50 and d 90 Value. For example, d 50 Values are based on the mean median of volume d 50 Particle size diameter.
[0161] Examples
[0162] The following examples further illustrate the present invention but should not be construed as limiting its scope.
[0163] 1. Preparation of the composite particles (p) to be applied according to the invention
[0164] In the following, a general production scheme is described, followed by two selected explicit production examples of individual composite particles. Finally, a general list of composite particles produced according to the general production scheme is provided.
[0165] 1.1 General production plan
[0166] Water and a commercially available aqueous solution of polyvinyl alcohol (10 wt.-%) are mixed to obtain mixture 1. Separately, a mixture 2 of a bismuth neodecanoate catalyst, optionally an organic solvent, and one or more monomers to be used to prepare a (meth)acrylate-based polymer is prepared. Mixture 2 is then emulsified into mixture 1 for 5 min at 18,000 rpm using, for example, a silent crusher (rotor stator dispersion tool) to produce an oil-in-water emulsion. An ice bath is used during the emulsification step to keep the temperature below 35°C. The emulsion is then transferred to a glass reactor equipped with an anchor stirrer and a water condenser and stirred at 130 rpm. Nitrogen is flowed in the reactor throughout the polymerization. A free radical initiator (thermal initiator) is then added to the medium and the temperature is increased: starting from 20°C, 75°C is reached over 60 minutes (linear rate). Then, the temperature is increased to 85°C (linear rate) within 60 minutes and maintained for 60 minutes. Afterwards, the system is cooled to room temperature (20°C) (linear rate) over 60 minutes. At the start of cooling, initiator (redox initiator pair) was added to the medium over a period of 50 minutes in order to reduce the residual monomer content.
[0167] The monomers applied were as follows: MMA: methyl methacrylate, tBMA: tert-butyl methacrylate, DMAPMA: dimethylaminopropyl methacrylamide, nBA: n-butyl acrylate, BDDA: 1,4-butanediol diacrylate. As an optional organic solvent, n-butyl acetate (BA) was applied. Vit C (L(+)-ascorbic acid) and tBHP (tert-butyl hydroperoxide) were applied as a redox initiator partner system.
[0168] 1.2a) Example 1: MMA / tBMA / DMAPMA / BDDA=60 / 25 / 5 / 10–K-Kat XK 651 / BA=75 / 25
[0169] Composite particles were prepared from (i) MMA / tBMA / DMAPMA / BDDA used in a ratio of 60 / 25 / 5 / 10 wt.-% and (ii) a 75 / 25 wt.-% mixture of K-Kat XK 651 (King Industries) as active catalyst and BA as solvent. The target ratio of metal-containing catalyst to polymer was 90 / 10 wt.-%. The target was a total active content of 32.15 wt.-% in the final dispersion.
[0170] First, an aqueous solution was prepared by diluting 270.0 g of a 10 wt.-% Mowiol 40-88 aqueous solution in 271.64 g of demineralized water and 2.16 g of a 2.5 wt.-% sodium nitrite aqueous solution. Then, an oil phase was obtained by mixing 364.5 g of K-Kat XK 651, 121.5 g of BA, 32.4 g of MMA, 13.5 g of tBMA, 2.7 g of DMAPMA and 5.4 g of BDDA. In a 2 L glass reactor, the oil phase was emulsified in the aqueous phase at 3,500 rpm using a laboratory dissolver equipped with a 5 cm diameter dissolver disk for 40 min. An ice bath was used during the emulsification step to keep the temperature of the emulsion below 35 ° C. The glass reactor was then equipped with an anchor stirrer and a water condenser and stirred at 130 rpm. Nitrogen was flowed in the reactor throughout the polymerization. 3.24 g of tert-butyl peroxyneodecanoate as a thermal initiator was added to the dispersion and the temperature was increased: starting from 20° C., it took 60 minutes to reach 75° C. (linear rate). Then, the temperature was increased to 85° C. (linear rate) within 60 min and maintained for 60 min. After that, the system was cooled to room temperature (20° C.) within 60 min (linear rate). At the beginning of cooling, 15.66 g of a 10 wt.-% tBHP aqueous solution was added within 3 min, while 30.94 g of a 10 wt.-% Vit C aqueous solution was continuously added to the medium over 50 minutes to reduce the residual monomer content.
[0171] In total, 1134 g of monodisperse composite particles (d 50 =1.5μm, d 90 =2.3 μm) in aqueous dispersion.
[0172] 1.2b) Example 2: MMA / DMAPMA / BDDA=80 / 5 / 15-K-Kat XK651
[0173] Composite particles were prepared from (i) MMA / DMAPMA / BDDA used in a ratio of 80 / 5 / 15 wt.-% and (ii) K-Kat XK 651 (King's Industries) as active catalyst. The target ratio of metal-containing catalyst to polymer was 90 / 10 wt.-%. The target was a total active content of 35.75 wt.-% in the final dispersion.
[0174] First, an aqueous solution was prepared by diluting 405g of a 10wt.-% Mowiol 40-88 aqueous solution in 160.95g of demineralized water and 4.32g of a 2.5wt.-% sodium nitrite aqueous solution. 0.03g of Tego Foamex 3062 defoamer was added. Then, an oil phase was obtained by mixing 486g of K-Kat XK 651, 43.2g of MMA, 2.7g of DMAPMA, and 8.1g of BDDA. In a 2L glass reactor, the oil phase was emulsified in the aqueous phase at 3,500rpm using a laboratory dissolver equipped with a 5cm diameter dissolver disk for 40min. An ice bath was used during the emulsification step to keep the temperature of the emulsion below 35°C. The glass reactor was then equipped with an anchor stirrer and a water condenser and stirred at 130rpm. 100g of demineralized water was added. Nitrogen was flowed in the reactor throughout the polymerization. 3.24 g of tert-butyl peroxyneodecanoate as thermal initiator are added to the dispersion and the temperature is increased: starting from 20° C., 75° C. is reached over 60 minutes (linear rate). The temperature is then increased to 85° C. over 60 min (linear rate) and maintained for 60 min. Thereafter, the system is cooled to room temperature (20° C.) over 60 min (linear rate). At the start of cooling, 30.94 g of a 10 wt.-% aqueous solution of Vit C are added over 3 min, while 15.66 g of a 10 wt.-% aqueous solution of tBHP are continuously added to the medium over 50 minutes to reduce the residual monomer content. Finally, when the temperature has almost reached 20° C., another 100 g of water are added.
[0175] In total, 1360 g of monodisperse composite particles (d 50 =1.4μm, d 90 =2.2 μm) in aqueous dispersion.
[0176] 1.3 List of composite particles
[0177] Table 1 shows the different composite particles prepared according to the general procedure outlined under 1.1.
[0178] Table 1
[0179]
[0180]
[0181] 2. Preparation of cathodically depositable aqueous electrodeposition coating material composition
[0182] 2.1 Pigment paste (II)
[0183] A standard pigment paste P1 commonly used in the preparation of cathodically depositable aqueous electrodeposition coating material compositions is prepared by (i) mixing the corresponding ingredients in a dissolver and (ii) grinding the mixture from (i) using a standard mill under conventional conditions.
[0184] Pigment paste P1 contains an aqueous dispersion of an epoxy-amine adduct as a grinding resin (i.e. a resin that meets the requirements of component (a), with a solid content of 40%, but is different from component (a) described below for binder dispersion (I)). In addition, paste P1 contains bismuth (III) subnitrate as a catalyst, carbon black as a black pigment and titanium dioxide as a white pigment, as well as kaolin as a filler. Water and additives conventionally used for cathodically depositable aqueous electrodeposition coating material compositions are applied as further ingredients. The solid content of pigment paste P1 is 65%. The amount of bismuth (III) calculated as bismuth metal is 4.26%, based on the total weight of pigment paste P1.
[0185] Pigment paste P2 was prepared in the same manner and with the same types and amounts of ingredients as pigment paste P1; however, with the difference that no bismuth(III) subnitrate was applied.
[0186] 2.2 Adhesive dispersion (I)
[0187] As standard adhesive dispersion (I), two systems commonly used in electrodeposition coating material compositions were used (adhesive dispersion (I).1 and adhesive dispersion (I).2). The adhesive dispersion contains an aqueous dispersion of an epoxy-amine adduct as an adhesive resin (component (a)), a blocked polyisocyanate as a crosslinking component (b) and also other ingredients, in particular such as conventional additives, organic cosolvents and water. The ingredients of the adhesive dispersion are added in a separate order, whereby different mixing (dissolution) steps and dispersion stages occur. The two adhesive dispersions differ in the type of crosslinker (b), i.e., blocked polyisocyanate, more particularly, the blocking agent of the blocked polyisocyanate. Therefore, adhesive dispersion (I).2 has a higher reactivity (i.e., a lower deblocking temperature of the blocked polyisocyanate). The solids content of the two adhesive dispersions is 38%.
[0188] 2.3 Electrodeposition coating material composition
[0189] By the above pigment paste and binder dispersion, an electrodeposition coating material composition was prepared.While the comparative system was prepared from pigment paste P1 and binder dispersion, the composition of the present invention was prepared from pigment paste P2, binder dispersion and also composite particles according to Example 2 above.
[0190] Details of each bath and its components are shown in Table 2. The components listed in the table were mixed with one another in this order, thereby forming an electrodeposition coating material composition for application (the following item 2.).
[0191] Table 2: Electrodeposition coating material composition
[0192]
[0193] 3. Electrodeposition coating of substrate
[0194] The coating films obtained from the electrodeposition coating material composition described above under item 2.3 were deposited on a cathodically connected test board at a deposition voltage between 200 V and 260 V (the deposition time was varied accordingly to produce a total charge of about 40-42 As) and a coating bath temperature of 32° C., and then baked for 15 minutes at a substrate temperature of 175° C. to obtain a coating thickness of about 20-22 microns. Thus, different amounts of phosphate were introduced into the bath before deposition, namely 0 ppm (control), 200 ppm and 400 ppm.
[0195] As test panels, cold rolled steel substrates ( GB26S 6800OC).
[0196] Table 3 shows a list of all cured coatings produced.
[0197] Table 3:
[0198]
[0199] 3. Characterization of coated substrates
[0200] According to the above method, the glass transition temperature Tg and also the acetone resistance of the cured coatings were investigated.
[0201] Table 4 shows the corresponding data on the corrosion test.
[0202] Table 4
[0203]
[0204]
[0205] These results indicate that the compositions and cured coatings of the invention show significantly enhanced film-forming and curing capabilities, respectively, under increased phosphate poisoning, through high glass transition temperatures and high acetone resistance. Specifically, while cured coatings B and C (and also H and I) show a significant decrease in film-forming and curing efficiency at phosphate levels of 200 ppm and 400 ppm, respectively, systems E and F (and K and L) of the invention still show the best film-forming behavior despite phosphate poisoning. Comparison of coatings B and C with H and I reflects the higher reactivity of binder dispersion (I).2 compared to dispersion (I).1. However, this higher reactivity cannot cope with phosphate poisoning, as systems H and I also do not show sufficient film-forming and cross-linking efficiency.
Claims
1. A cathodic-depositable aqueous electrodeposition coating material composition comprising (I) at least one binder dispersion comprising at least one cathodically depositable polymer (a) and at least one crosslinker component (b), (II) at least one pigment paste containing at least one pigment and / or filler (c) and at least one polymer as grinding resin, The composition further comprises at least one type of composite particles (p), the composite particles comprising at least one metal-containing catalyst (pc) and at least one (meth)acrylate polymer (mp).
2. The cathodically depositable aqueous electrodeposition coating material composition according to claim 1, wherein: At least one epoxide-amine adduct is present as at least one polymer (a).
3. The cathodically depositable aqueous electrodeposition coating material composition according to claim 1 or 2, wherein: As at least one crosslinking agent (b) at least blocked polyisocyanate is present.
4. The cathodically depositable aqueous electrodeposition coating material composition according to any one of claims 1 to 3, wherein: The metal-containing catalyst (pc) is a bismuth (III)-containing catalyst.
5. The cathodically depositable aqueous electrodeposition coating material composition according to any one of claims 1 to 4, wherein: The polymer (mp) comprises a monomer mixture consisting of at least: (a) 40 to 98% by weight of C1-C16 (meth)acrylic acid; 10 -alkyl esters, (b) 2 to 45% by weight of polyethylenically unsaturated monomers and (c) 0 to 20% by weight of monoethylenically unsaturated monomers other than monomer (a).
6. The cathodically depositable aqueous electrodeposition coating material composition according to any one of claims 1 to 5, wherein: The polymer (mp) is prepared in the presence of the metal-containing catalyst (pc).
7. A method for producing composite particles (p) comprising at least one metal-containing catalyst (pc) and at least one (meth)acrylate polymer (mp), wherein the polymer (mp) is prepared in the presence of the metal-containing catalyst (pc), the method comprising the following steps: (1) preparing an oil-in-water emulsion in which the monomers for producing the polymer (mp) and the metal-containing catalyst are part of or are a dispersed phase in an aqueous medium, (2) polymerizing the monomers in the oil-in-water emulsion of step (1) by an initiator.
8. The method according to claim 7, wherein: The oil-in-water emulsion of step (1) comprises at least one dispersant.
9. Composite particles (p) prepared according to the process of claim 6 or 7, comprising at least one metal-containing catalyst (pc) and at least one (meth)acrylate polymer (mp).
10. A method for producing a cathode-depositable electrodeposition coating material composition, comprising: - providing at least one binder dispersion (I) comprising at least one cathodically depositable polymer (a), - providing at least one pigment paste (II) comprising at least one pigment and / or filler, - mixing the binder dispersion (I), the pigment paste (II) and any further potential components of the composition, At least one component of the composition comprises at least one type of composite particles (p), the composite particles comprising at least one metal-containing catalyst (pc) and at least one (meth)acrylate polymer (mp).
11. A method for at least partially coating a conductive substrate by cathodic electrodeposition coating, the method comprising at least steps (1) to (5), namely (1) at least partially immersing the conductive substrate in an electrodeposition coating bath comprising the electrodeposition coating material composition according to any one of claims 1 to 6, (2) connecting the substrate as a cathode, (3) depositing a coating film obtained from the electrodeposition coating material composition on the substrate using direct current, (4) removing the coated substrate from the electrodeposition coating bath, and (5) Baking the coating film deposited on the substrate.
12. An electrically conductive substrate at least partially coated with an electrodeposition coating material composition in baked form according to any one of claims 1 to 6 and / or produced according to claim 10 and / or obtainable by a process according to claim 11.
13. A method for improving the phosphate stain resistance of a cathodically depositable aqueous electrodeposition coating material composition, the method comprising adding to the electrodeposition coating material composition at least one type of composite particles (p), the composite particles comprising at least one metal-containing catalyst (pc) and at least one (meth)acrylate polymer (mp).
14. The method according to claim 13, wherein: The polymer (mp) is prepared in the presence of the metal-containing catalyst (pc).
Citation Information
Patent Citations
use of microcapsules in plasterboard
DE10139171A1
Aqueous binder dispersion for cationic electrocoating lacquers
DE19703869A1
Aqueous coating composition and process for producing a multilayer coating
DE19712940A1
WATER-DILUBLE BINDERS FOR CATIONIC ELECTROCOATS AND PROCESS FOR THEIR MANUFACTURE
DE3518732A1
Water-dilutable binders for cationic electrocoatings and methods for their production
DE3518770A1